Functional diversity of shredders, not species richness, drives the decomposition rate of leaf litter in ponds - Dekanová, Vladimíra; Novikmec, Milan; Svitková, Ivana; Svitok, Marek (Frontiers in Ecology and Evolution, 2023)
Leaf litter decomposition is a critical ecosystem-level process in many freshwater habitats. Although ponds are likely to derive a large proportion of their energy from riparian vegetation, allochthonous organic matter decomposition in these water bodies has received little attention. We studied the breakdown rates of black alder (Alnus glutinosa (L.) Gaertn.) litter in ponds and provide the first evidence of the role of the taxonomic and functional diversity of pond-dwelling shredders in this ecosystem process. Despite a strong connection to riparian zones, the litter breakdown rates observed in ponds were generally lower than those reported in headwater streams. It seems that ponds provide less favorable conditions for shredder communities than headwaters. The rate of organic matter decomposition in ponds was significantly positively related to functional diversity, represented by the variability of shredder body size, while shredder species richness did not appear to be a reliable proxy for this ecosystem function. This finding is consistent with theoretical predictions that functional complementarity among species has a systematic effect on ecosystem processes. It also emphasizes that body size is a crucial functional trait mediating the effects of shredder diversity on litter decomposition in ponds.